Stimulating Effect of Salicylic Acid in the In Vitro and In Vivo Culture of Vanilla (Vanilla planifolia Jacks.) - Ortega-Macareno, Luis C.; Iglesias-Andreu, Lourdes G. (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
Vanilla planifolia Jacks., is the only commercially cultivated orchid for its compound vanillin. This crop has had serious production limitations due to its susceptibility to Fusarium oxysporum f. sp. vanilla (Fov). Salicylic acid (SA) regulates growth and development processes and induces resistance in plants. Our study evaluated its effect on the growth and development of V. planifolia seedlings grown in vitro and in vivo. A completely randomized design was used with seedlings obtained from nodal segments (2-3 cm long) grown in MS medium with different concentrations of SA (0, 0.25, 5, and 7.5 μmol). An experimental design with four SA concentration treatments (0, 0.25, 0.5, and 1 mmol) and 12 replications was used to evaluate the effects of SA on greenhousegrown plantlets. During four weeks, the number of shoots, length, thickness, number of leaves, number and length roots, chlorophyll and carotene content for both conditions were observed. We found the 7.5 μmol and 1 mmol SA stimulated the growth and development of vanilla plantlets grown both in vivo and in vitro. SA does not affect the content of photosynthetic pigments under any growth conditions.